Metode Tutor Sebaya Untuk Pembelajaran Penguasaan Ragam Gerak Tari Monamot Di Gorontalo - Winda Mahaputri; Riana Diah Sitharesmi; Rahmawati Ohi; Nurlia Djafar; Ipong Niaga (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the process of learning the Monamor Dance through the peer tutoring method in the dance extracurricular program at SMA Negeri 1 Suwawa Timur and to identify the supporting and inhibiting factors. The limited time allocated to dance practice in formal classroom instruction has prompted the use of extracurricular activities as intensive training spaces to preserve local cultural heritage. This study employed a descriptive, qualitative approach with a single-case study design. The participants consisted of 10 female students, of whom two eleventh-grade students acted as tutors due to their higher level of competence, while the remaining eight students served as tutees. Data were collected through direct observation, interviews, questionnaires, and activity documentation. Data validity was ensured through reference materials, source triangulation, and technique triangulation. The findings revealed that the stages of learning through the peer tutoring method included identifying students' initial abilities, selecting tutors, forming groups, practicing movement sequences, adjusting movements to musical accompaniment and props, conducting full rehearsals, and performing in the final presentation. The implementation of this method was found to improve students wiraga (movement technique), wirama (rhythm), and wirasa (expression), while also fostering leadership skills and group collaboration. Supporting factors included students' high motivation, the comfort of practicing with peers, and the availability of facilities such as costumes and props. Meanwhile, inhibiting factors included students' initial reluctance to ask questions, a lack of seriousness due to close peer relationships, tutors" limited experience in providing guidance, and scheduling conflicts regarding the use of practice spaces